Wild Mammals and birds used by inhabitants of the Abujao river basin (Ucayali, Peru) - Vela Alvarado, Jorge Washinton (2017)
The Peruvian Amazon is classified as one of the mega-diverse ecosystem of the world. Local populations have benefited from the uses of its richness of fauna and flora, promoting the emergence of a wide variety of uses. The Abujao river basin, located in the Peruvian Amazon, is home for mestizos and indigenous groups of Ashéninka and Shipibo-Conibo, whose traditions, and ancestral and ecological knowledge are still alive and closely related to their natural environments. This research was carried out to determine how and to what extent present groups of indigenous and mestizo in the Abujao river basin have been using the wild species of mammals and birds in their locations. Categories of its uses were determined. Among of all defined categories, the most predominant one was the use of wild animals for human consumption, traditional medicine and commercial trades. In contrast, relatively few species, in whole or part, were still used for rituals, and ornamental due to the loss of some ancestral knowledge and traditions on these uses. Revaluing this set of knowledge and uses has a great importance in the conservation of birds and mammals as well as the ecological knowledge of local populations in the Peruvian Amazon.